Characterization Of Organic Solvent Tolerant Halo-Alkalithermostable Amylase From Bacillus Cereus Ocw 3(1) - VISHAL R DHUNDALE (International Journal of Pharma and Bio Sciences, 2015)
A bacterium-OCW 3(1) with an ability to produce extracellular halophilic, alkali-tolerant, organic solvent stable, and moderately thermostable amylase was isolated from Lonar soda lake India. Identification of the bacterium was done based upon biochemical tests and 16S rDNA sequence. The result of gene sequence analysis indicated that bacterium strain OCW3(1) shows highest degree of similarities with Bacillus cereus. Further this strain was screened for the amylolytic activity using starch agar plates and results indicated that it was amylase producer. The optimum amylase production was achieved at pH 10 and70ºC temperature in the medium containing 3%NaCl and 1%(w/v) starch. The enzyme was active over a range of 2–10% sodium chloride examined in culture broth. The optimum amylase activity was observed at 2% sodium chloride. The results showed that fructose was the best carbon source and yeast extract and peptone was the best nitrogen source. The activity of amylase was optimum when 2% NaCl and starch was used in media for production. There was highest enzyme activity at temperature of 70°C, pH 11, 1.5 mL enzyme concentration and 35 min of incubation period. Kinetic properties such as Km and Vmax were 10 mg/mL and 58.82 mol/min/mL, respectively. Enzyme activity strongly inhibited by heavy metals such as BaCl2, CuCl2, CaCl2, MnSO4, ZnSO4 and KCl. Amylase was found to be stable and enhance by organic solvents such as Methanol, Acetone, 1-Butanol, Benzene, Toluene and Chloroform which has showed demonstrating the unique properties of amylase enzymes. From the results it was concluded that the enzyme is a haloalkaline, thermostable and organic solvent tolerant in nature. The determination in the present study, an enzyme production analysis was conducted to address this Bacillus cereus OCW3(1) as a potential for biotechnology application. To our knowledge, this study represents the first report of considering that, amylase enzymes could be further explored in their differential functionality for industrial application and for genetic breeding leading to higher production levels.